INSIGHT INTO MECHANISM UNDERLYING THE MEDICINAL USE OF CYDONIA OBLONGA IN GUT AND AIRWAYS DISORDERS - K. H. Janbaz; A. Shabbir; M. H. Mehmood; A. H. Gilani (Journal of Animal and Plant Sciences, 2013)
This study was intended to provide the pharmacological rationalization for the medicinal use of Cydonia oblonga in gut and airways diseases. Results showed that the crude extract of Cydonia oblonga seeds (Co.Cr) produced atropine- sensitive spasmodic effects in isolated ileum of guinea-pig and rabbit jejunum preparations. In rabbit jejunum, Co.Cr also showed relaxant activity at slightly higher concentrations (0.1-10 mg/mL). When analyzed on rabbit jejunumprecontracted with K + (80 mM), the plant extract (0.003-10 mg/mL) produced relaxation. A rightward shifting of Ca++ dose-response curves along with decline in the maximum response was observed after pretreatment with Co.Cr (0.003- 0.01 mg/mL), which was similar to the effect of verapamil. The plant extract (0.01-10 mg/mL) relaxed CCh (1 µM) and K + (80 mM)-induced contractions of isolated rabbit tracheal preparations, similar to the effect produced by verapamil. Data show that Cydonia oblonga possesses spasmogenic effect mediated through cholinergic pathway, while Ca++ antagonist like mechanism is found responsible for its spasmolytic activity, thus provides justification for the medicinal use of the plant in gut and airways disorders
Keywords: Cydonia oblong; Spasmodic; Cholinergic; Antispasmodic; Ca antagonist; Gut; Trachea